Commune-level estimation of poverty measures and its application in Cambodia - Tomoki Fujii (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2004)
In this study, we combined the Cambodian socioeconomic survey for 1997 and the country's population census of 1998 to produce poverty measures at the commune-level in Cambodia using the small-area estimation technique developed by Elbers, Lanjouw and Lanjouw. While there are a number of communes for which the standard errors associated with the estimates are too high, we found that they are on average small enough to be useful. We illustrate the application of poverty maps with reference to education programmes.
Keywords: O20; I28; I32; 330; poverty mapping; Cambodia; targeting; education; Armut; Messung; Kambodscha